Study of inclusion problem in Morrey space - Hussein , Manal; Ali , Mohammad; Suliman , Haydar (Latakia University Journal -Basic Sciences Series, 2019)
In this research we study one of the functional analysis problems, it is inclusion of functional spaces. We study especially the inclusion of spaces which branches from Morrey spaces . First, we mentioned some of the results that have been reached in the field of inclusion of some of the famous functional spaces such as Holder, Lebesgue, Orlicz and Morrey spaces. We then defined by introducing a new parameter to define the Morrey space and then studied some of its properties. Moreover, we presented the theorem that studies the inclusion between and Morrey space in addition to the theorem that studies the inclusion between and Lebesgue space. Finally, we studied in three cases the inclusion of functional spaces ,and we found that the parameters and play the key role in the inclusion of these spaces.